2017
DOI: 10.1111/coa.12872
|View full text |Cite
|
Sign up to set email alerts
|

Role of transnasal flexible laryngo‐oesophagoscopy (TNFLO) in investigating patients with globus symptoms

Abstract: A total of 218 patients were recruited in this study. Positive findings included upper aerodigestive cancers in two patients, other pathologies included reflux (four patients), cricopharyngeus-related pathologies (19 patients), candida (five patients). There were only five re-referrals of patients who were discharged following normal examination with TNFLO. In nine patients, TNFLO could not be completed and they went on to have other diagnostic procedures CONCLUSION: This article is the largest to date in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Success rate of obtaining a TNE‐guided biopsy is smaller than that of TNE alone (86% vs. 94%) . This can be explained by patient anxiety, which is understandingly more due to the presence of a lesion, and the extra time needed for the procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Success rate of obtaining a TNE‐guided biopsy is smaller than that of TNE alone (86% vs. 94%) . This can be explained by patient anxiety, which is understandingly more due to the presence of a lesion, and the extra time needed for the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Success rate of obtaining a TNE-guided biopsy is smaller than that of TNE alone (86% vs. 94%). 23 This can be explained by patient anxiety, which is understandingly more due to the presence of a lesion, and the extra time needed for the procedure. Additionally, factors such as a strong gag reflex, persistent cough, and narrow nasal passages were among reasons leading to patients not tolerating the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Routine ENT practice, particularly for investigating globus, is to use barium swallow as a screening test for oesophageal pathology, and this has a diagnostic yield for malignancy of 0%‐1% . There is, however, evidence to suggest that the initial clinical presentation of as many as 30% of patients with oesophageal cancer is only with laryngopharyngeal reflux (LPR) symptoms, and in particular, the presence of more than one LPR symptom significantly increases the risk of the presence of oesophageal cancer or Barrett's oesophagus (Figure ) .…”
Section: Discussionmentioning
confidence: 99%
“…Routine ENT practice, particularly for investigating globus, is to use barium swallow as a screening test for oesophageal pathology, and this has a diagnostic yield for malignancy of 0%-1%. [12][13][14][15][16] There is, however, evidence to suggest that the initial clinical presentation of as many as 30% of patients with oesophageal cancer is only with laryngopharyngeal reflux (LPR) symptoms, and in particular, the presence of more than one LPR symptom significantly increases the risk of the presence of oesophageal cancer or Barrett's oesophagus (Figure 5). 17 Whether therefore direct oesophageal visualisation using transnasal oesophagoscopy should be used in all patients with globus and LPR symptoms, on the basis that it represents a novel diagnostic opportunity for earlier identification of oesophageal cancer, 17 whilst also improving the management of benign causes of globus and extra-oesophageal reflux, 16,[18][19][20][21][22] awaits a consensus opinion.…”
Section: Synopsis Of Key Findingsmentioning
confidence: 99%
“…However, there were no differences in videofluoroscopy between healthy adults and patients with globus in terms of in hyoid bone displacement, pharyngeal transit time, pharyngeal constriction ratio, or maximum opening of the esophageal entrance, suggesting that no pharyngeal motor dysfunction is present or that findings on testing may not necessarily be linked to globus as a symptom 13 . Benign findings noted on videofluoroscopy in a prospective study of 218 globus patients included reflux changes (2%), candida esophagitis (2%), and cricopharyngeal dysfunction (9%); the likelihood of finding upper aerodigestive tract cancers was <1% 14 . Other studies have reported no diagnostic benefit in performing videofluoroscopy, barium esophagram, and thyroid ultrasound in patients with idiopathic globus and negative ENT evaluation 15,16 .…”
Section: Etiology Of Globusmentioning
confidence: 99%